2020
DOI: 10.3389/fgene.2020.591984
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Profile of the SNAT Gene Family in Tobacco (Nicotiana tabacum)

Abstract: Melatonin plays key roles in development and confers stress tolerance to plants. Serotonin N-acetyltransferase (SNAT) is either the enzyme involved in the last step or the penultimate enzyme of phytomelatonin biosynthesis. To date, SNAT genes have not been characterized in tobacco (Nicotiana tabacum), an economically important plant species. The sequence of the Acetyltransf_7 conserved domain was used as a query sequence, and 12 NtSNAT candidate genes were in turn identified in the genome of tobacco. These NtS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
(43 reference statements)
1
6
0
Order By: Relevance
“…A total of 14 potato genome StALMT family members are consistent with corresponding members in the publicly reported Arabidopsis ( Kovermann et al., 2007 ). More than 12 ALMT family members in peach and Chinese plum ( Lin et al., 2018 ), 16 ALMT family members in strawberry ( Lin et al., 2018 ) and tomato ( Sasaki et al., 2016 ), 21 family members in apple ( Lin et al., 2018 ), 25 family members in European pear ( Lin et al., 2018 ), 27 family members in Chinese white pear ( Lin et al., 2018 ), 30 family members in common tobacco ( Zhang et al., 2020 ), and 34 family members in soybean have been identified ( Peng et al., 2018 ). In our study, we found 14 ALMT family members in the potato that are distributed on seven different chromosomes ( Figure 1 ); this is similar to the findings reported on the chromosomal distribution of ALMT family members in other species ( Ma et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 14 potato genome StALMT family members are consistent with corresponding members in the publicly reported Arabidopsis ( Kovermann et al., 2007 ). More than 12 ALMT family members in peach and Chinese plum ( Lin et al., 2018 ), 16 ALMT family members in strawberry ( Lin et al., 2018 ) and tomato ( Sasaki et al., 2016 ), 21 family members in apple ( Lin et al., 2018 ), 25 family members in European pear ( Lin et al., 2018 ), 27 family members in Chinese white pear ( Lin et al., 2018 ), 30 family members in common tobacco ( Zhang et al., 2020 ), and 34 family members in soybean have been identified ( Peng et al., 2018 ). In our study, we found 14 ALMT family members in the potato that are distributed on seven different chromosomes ( Figure 1 ); this is similar to the findings reported on the chromosomal distribution of ALMT family members in other species ( Ma et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Solanaceae plant, SlSANT (tomato) and CsSNAT (cucumber) had conservative functions in salt resistance, while exhibiting distinct roles in heat tolerance 53–56 . NtSNAT1/2 are highly homologous to the characterized OsSNAT1 (62.95% and 71.36%) that were also potentially associated with increasing high temperature and Cd resistance 57 . Ectopic expression of HpSNAT1/2 , VvSNAT1/2 , MsSNAT , and MzSNAT5 could protect Arabidopsis from salinity, drought, salt, and Cd damage 58–64 .…”
Section: Melatonin Biosynthesismentioning
confidence: 99%
“…Upregulation of CsSOD , CsCAT , CsP5CS1 , CsPIP , CsP5CS2 and CsHSP90 improved the salt tolerance of CsSNAT overexpressed cucumber 55 . HSP40 gene also involved in high‐temperature tolerance of tobacco 57,68 . SlASMT and GmASMT could promote the protection of cellular proteins in plants through the induction of transcription factors ( NAC , MYB , WRKY , HSPs , and ERF ), autophagy, and stress signaling under heat and drought stresses 68 .…”
Section: Melatonin Biosynthesismentioning
confidence: 99%
“…Recently, the functional genes responsible for the Mel pathway have been revealed in rice following a homologous sequence alignment strategy. 20,22,57,73 Similarly, some candidate genes have been functionally validated in various plant species, 24,26,[74][75][76] indicating that the reverse-genetics scheme is effective. Nevertheless, this approach usually necessitates intensive labor input, especially for polyploid species.…”
Section: Candidate Gene Identification Through Mgwas In Wheatmentioning
confidence: 99%